2015
DOI: 10.1016/j.yhbeh.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle phase affects discrimination of infant cuteness

Abstract: Please cite this article as: Lobmaier, Janek S., Probst, Fabian, Perrett, David I., Heinrichs, Markus, Menstrual cycle phase affects discrimination of infant cuteness, Hormones and Behavior (2015),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Past research has identified sex differences with regard to cuteness (Lobmaier et al, 2015(Lobmaier et al, , 2010. In the present studies, we also observed that females were more likely to score higher on our main variables such as cuteness, empathy, or caretaking, while simultaneously providing lower scores on the willingness to eat the advertised meat.…”
Section: The Evolutionary Importance Of Cutenesssupporting
confidence: 76%
See 1 more Smart Citation
“…Past research has identified sex differences with regard to cuteness (Lobmaier et al, 2015(Lobmaier et al, , 2010. In the present studies, we also observed that females were more likely to score higher on our main variables such as cuteness, empathy, or caretaking, while simultaneously providing lower scores on the willingness to eat the advertised meat.…”
Section: The Evolutionary Importance Of Cutenesssupporting
confidence: 76%
“…These sex differences have been suggested to be based on evolutionary and biological aspects. Providing support for this notion, females reported a better discrimination of cute and non-cute infant faces during ovulation (Lobmaier, Probst, Perrett, & Heinrichs, 2015). In addition, young women and premenopausal females performed better at detecting cuteness differences than older women or men did (Sprengelmeyer et al, 2009).…”
mentioning
confidence: 79%
“…Whereas serum 17β‐estradiol shows a preovulatory as well as luteal phase peak, salivary 17β‐estradiol shows only a transient preovulatory increase, but not the expected increase in the luteal phase (Lu et al, ; Chatterton et al, ). Thus, some studies quantifying salivary 17β‐estradiol do not identify significant differences across the menstrual cycle phase (e.g., Andreano and Cahill, ; Lobmaier et al, ; present study). In contrast to 17β‐estradiol, salivary progesterone level reliably distinguishes between follicular and luteal women (e.g., Andreano and Cahill, ; present study).…”
Section: Discussioncontrasting
confidence: 51%
“…Two studies to date have investigated potential differences in responses to infant faces across the menstrual cycle. One of these did not find any effects (Sprengelmeyer et al, 2013 ), however the other using a forced-choice paradigm where subjects indicated which of two infant faces was cuter, found that women were more likely to choose the cuter baby during their ovulatory than luteal phase of the cycle (Lobmaier et al, 2015 ). Nevertheless, cuteness discrimination was not associated with saliva concentrations of oestradiol, progesterone or testosterone, leading the authors to speculate that this menstrual cycle phase effect might be associated with other relevant hormones which change during the cycle, such as oxytocin or prolactin.…”
Section: Hormonal Correlates Of Attraction To Infant Facesmentioning
confidence: 99%